Forecasting the Ambon City Consumer Price Index Using Arima Box-Jenkins - Jefry Esna T. Radjabaycole; Ronald John Djami; Gabriella Haumahu (Tensor: Pure and Applied Mathematics Journal, 2021)
The Consumer Price Index is an index number that measures the average price of goods and services consumed by households. The index number is the price comparison in a certain month against the previous month, in which case the price in the previous month is the price in the base year in the CPI calculation. CPI is time series data, so CPI data in the next period can be known by forecasting through time series analysis. Arima is a technique for finding the most suitable pattern from a group of data (curve fitting). Based on the results of the analysis, the best ARIMA model used in forecasting CPI in Ambon city for the period January 2007 to December 2020 is the ARIMA model (1,1,1), namely 1 = 0.9000 and 1 = 0.9933.